Transport-geographic continentality of Canada: from sea to sea - Anastasia Lomakina (European Regional Science Association (ERSA), 2014)
Maritime location of Canada has not been questioned by many generations of researchers. However, a quick look at the map or the coastline measurements do not always allow to identify the real sources of its inalienable properties. Canada ranks first in coastline in the world and is formally "the most maritime country of the planet". At the same time traditional approach of estimation of maritime location used separately would not allow judging the extent of so-called maritimeness of Canada, and the combined use of different approaches could lead to discrepant results. In our study we have used a method proposed by L. Bezrukov, which yields to estimate continental location in transport-geographic terms. This method enables us to give the integral assessment of maritime location of Canada based on population distribution and the impact of inland waterways suitable for sea transport. The estimate proves that there is in Canada an interesting mix of giant inland spaces and vast seaside regions, which in combination with the natural geographic and socio-economic factors leads to a 'multidimensional' maritime position and curious territorial organization of economy and population distribution. The estimate proves that Canada is a country with low continental degree. However, maritimeness of modern Canada is defined not by coastline length or interocean position but by ample development of hand-made inner water ways, which lowered continentality of Canadian eucumene by having increased transport, economic and geographical access to the sea. Comparison of transport-economic and transport-geographic remoteness from the sea confirm the constant influence of these unique seaways. This suggestes the conclusion that Canadians themselves have made their country maritime. Paradoxical conclusion was that in different parts of Canada maritime influence is not always defined by distance to the sea. For Canada, there is another unexpected pattern: the further north is, the higher the degree of transport-geographic continentality. Population and economy, originally developed in these transport and geographical conditions, are mainly located in coastal and maritime areas in their new, non-traditional interpretation. Ultracontinental territories compensate unfavorable interior and landlocked location, using the continental neighbourhood. Overall, Canada demonstrates a successful realization of its maritime potential. It was prouved by estimation of adducted transportation share of economy that confirmed considerable de facto cost reduction of transport work owing to sea transport use.
Keywords: P48; 330; Canada; economic-geographical location; maritime location; transport; continentality